2020
DOI: 10.1038/s41598-020-64840-5
|View full text |Cite
|
Sign up to set email alerts
|

Structural variability of dyads relates to calcium release in rat ventricular myocytes

Abstract: Cardiac excitation-contraction coupling relies on dyads, the intracellular calcium synapses of cardiac myocytes, where the plasma membrane contacts sarcoplasmic reticulum and where electrical excitation triggers calcium release. The morphology of dyads and dynamics of local calcium release vary substantially. To better understand the correspondence between the structure and the functionality of dyads, we estimated incidences of structurally different dyads and of kinetically different calcium release sites and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 46 publications
1
17
0
Order By: Relevance
“…Because JPH2 is thought to improve coupling between LTCC and RyRs ( 1 4 ), it is likely that the integrity of EC coupling junctions ameliorated secondary to increased JPH2 expression, even though there was no t-system recovery ( Figure 7 ). This would fit to observations of high plasticity of junctophilin-2 and ryanodine receptors ( 4 ) and to the observation that Ca 2+ release is more rapid and more efficient in compact dyads, i.e., EC coupling junctions of high integrity ( 58 ). Investigating this idea in more detail and finding ways to induce reverse remodeling of EC coupling junctions could be promising targets of future studies.…”
Section: Discussionsupporting
confidence: 67%
“…Because JPH2 is thought to improve coupling between LTCC and RyRs ( 1 4 ), it is likely that the integrity of EC coupling junctions ameliorated secondary to increased JPH2 expression, even though there was no t-system recovery ( Figure 7 ). This would fit to observations of high plasticity of junctophilin-2 and ryanodine receptors ( 4 ) and to the observation that Ca 2+ release is more rapid and more efficient in compact dyads, i.e., EC coupling junctions of high integrity ( 58 ). Investigating this idea in more detail and finding ways to induce reverse remodeling of EC coupling junctions could be promising targets of future studies.…”
Section: Discussionsupporting
confidence: 67%
“…Recent experimental and theoretical studies established the importance of dyad structure and RyR clustering on spontaneous calcium spark formation (Cannell et al, 2013;Walker et al, 2014;Walker et al, 2015;Kolstad et al, 2018;Cosi et al, 2019) as well as on triggered calcium release (Zahradnik et al, 2013;Cosi et al, 2019;Novotova et al, 2020). In this study we used a large set of CRS geometries that approximated the structural data by constrained random distribution of RyRs in CRS (Iaparov et al, 2017;Iaparov et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The structure of dyads studied by electron microscopy revealed common features in their construction (Franzini-Armstrong et al, 1999;Hayashi et al, 2009) as well as substantial structural variability (Novotova et al, 2009;Novotova et al, 2013;Novotova et al, 2020). Super-resolution localization studies revealed tendency of RyRs to form irregular clusters of variable size and surface density (Baddeley et al, 2009;Hou et al, 2015;Macquaide et al, 2015;Galice et al, 2018;Jayasinghe et al, 2018;Kolstad et al, 2018;Asghari et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The structure of terminal cisternae studied by EM revealed common features in their construction ( Franzini-Armstrong et al, 1999 ; Hayashi et al, 2009 ) as well as their substantial structural variability ( Novotova et al, 2009 ; Novotova et al, 2013 ; Novotová et al, 2020 ). Super-resolution localization studies revealed a tendency of RYRs to form irregular clusters of variable size and surface density ( Baddeley et al, 2009 ; Hou et al, 2015 ; Macquaide et al, 2015 ; Galice et al, 2018 ; Jayasinghe et al, 2018 ; Kolstad et al, 2018 ; Asghari et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%